Upaya Aparat Kepolisian Dalam Menanggulangi Tindak Pidana Pencurian Dengan Kekerasan - Prakoso, Adityo Putro (Fakultas Hukum Universitas Wahid Hasyim, 2020)
Violent theft has long existed on earth, which should have been eradicated. The reality is that there is still a lot of theft with violence in modern times like today. Crime theft with violence is a very complex problem that can not be separated from social factors, especially economic. This is interesting to do research to get a picture of the eradication of acts of theft with violence. The purpose of this research about the crime of theft with violence is to get a picture of efforts to tackle violence and violence, and to get a picture of the difficulties to increase public awareness who should participate in efforts to eradicate theft with violence. The research method used is normative juridical. Results of the study give the picture that theft by violence is a form of crime. In connection with the rampant crime cases of theft with violence will cause special attention and encourage similar operations to be held. The success of the Curas operation will not succeed without the support and participation of the community.